If

```
3 2 = 7
5 4 = 23
7 6 = 47
9 8 = 79
```

Then

```
10 9 = ??
```

+6 votes

+3 votes

Given series is,

ODD EVEN = RELATION

3 2 7 ( 3*2+1)

5 4 23 (5*4+3)

7 6 47 (7*6+5)

9 8 79 (9*8+7)

Following the series we concluded that, Next term in this series must be,

11 10 119 (11*10+9)

But for confusing, the question term is of different nature of,

10 9 ??

Hence the problem is from a complete series of the following type,

3 2 7 ( 3*2+1)

4 3 14 (4*3+2)

5 4 23 (5*4+3)

6 5 34 (6*5+4)

7 6 47 (7*6+5)

8 7 62 (8*7+6)

9 8 79 (9*8+7)

10 9 98 (10*9+8)

11 10 119 (11*10+9)

Hence the answer must be 98

+1 vote

+1 vote

I'm curious, why a*b+(b-1)= isn't the correct formula?

it gives correct answer for all given

3 2 = 7

5 4 = 23

7 6 = 47

9 8 = 79

and also does answer for any other numbers, like

5459 5458 = 29800679

and you should not to make calculations like

3+2+2=7

5+4+2+3+2+7=23

7+6+2+5+4+23=47

9+8+2+7+6+47=79

10+9+2+9+8+79=117

where you need to complete all middle steps to get the correct answer in further numbers

or if I'll remove a line from original example:

3 2 = 7

5 4 = 23

deleted line

9 8 = 79

so the "third" line of this example appears to be wrong if we need to sum 9*8 with 5 instead of 7 - 9*8+5=77

so it's can't be the correct answer.

but a*b+(b-1)= works same here.

maybe not all must be too complicated?

IMO

0 votes

–1 vote

–1 vote

...